4.3 The Relationship Between Cause and Timing of Previous Stillbirth and the Risk of Stillbirth in Second Pregnancies. (26th April 2013) - Moraitis, AA; Smith, GC
Abstract : Background: Women with a previous stillbirth are at increased risk of stillbirth in their second pregnancy. However, there is little information on the relationship between the cause and timing of stillbirth in the first pregnancy and the risk in the second. Methods and Results: We identified 244, 122 records in nationally collected Scottish data with complete information on their first and second births. The risk of stillbirth in the second pregnancy was 2.7 per 1, 000 among 242, 800 women with previous live birth and 15.9 per 1, 000 among 1, 323 women with previous stillbirth (odds ratio [OR] = 5.95 [95% CI 3.84–9.22] p < 0.001). Adjustment for maternal characteristics had no material effect. The risk was similarly elevated for different causes of stillbirth in the first pregnancy. It was also similarly elevated whether the previous stillbirth was extreme preterm (24–32 weeks) or late preterm/term (33–43 weeks). However, the association in the second pregnancy significantly varied across the range 24–43 weeks (test of proportional hazards assumption p = 0.01). Previous stillbirth was strongly associated with the risk at 24–28 weeks (15.66 [8.44–29.05], P < 0.001), at 29–32 weeks (5.16 [1.64–6.27], P = 0.005) and 33–36 weeks (6.03 [2.47–14.72], P < 0.001) but there was no significant association at term (1.7 [0.42–6.82]), probably due to routine elective delivery at 37–38 weeks. Conclusion: Previous stillbirth is a strong risk factor for stillbirth in second pregnancies irrespective of the cause of the first stillbirth. The recurrence risk is much higher at extreme preterm gestational ages, but is still present at 33–36 weeks.